2018
DOI: 10.11591/ijeecs.v12.i1.pp38-45
|View full text |Cite
|
Sign up to set email alerts
|

Modified Blowfish Algorithm

Abstract: Cryptography guarantees security in communication through encryption. This paper proposed a modified Blowfish encryption that uses 128-bit block size and 128-bit key to comply with minimum requirements as an encryption standard. The modification retained the original structure for easy migration but utilized two S-boxes to save memory. A derivation was added to prevent symmetry.  The algorithm’s performance was evaluated using time, and avalanche. Upon testing, the modified blowfish is slower with key, encrypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Moreover, the modified AES has an improvement of 14.79% and 13.87% in round 2 and round 3 respectively. Consequently, an increase in the average results of the avalanche effect of the modified AES rivaled with the standard AES is evidently shown in Figure 6, the increase in avalanche effect also indicates an increase in security compared to the standard AES [21], [22]. The overall improvement of the modified AES in the avalanche effect over the standard AES is about 7%.…”
Section: Results and Analysismentioning
confidence: 90%
“…Moreover, the modified AES has an improvement of 14.79% and 13.87% in round 2 and round 3 respectively. Consequently, an increase in the average results of the avalanche effect of the modified AES rivaled with the standard AES is evidently shown in Figure 6, the increase in avalanche effect also indicates an increase in security compared to the standard AES [21], [22]. The overall improvement of the modified AES in the avalanche effect over the standard AES is about 7%.…”
Section: Results and Analysismentioning
confidence: 90%
“…The modification using multiple S-boxes indicated that it is the fastest among the algorithms, but suffered greatly in the avalanche effect test where it did not meet the mean value of 50% for all the plaintexts used. A very low value for the avalanche effect compromises the security of the encryption algorithm [24].…”
Section: Avalanche Effectmentioning
confidence: 99%
“…g) Approximate Entropy Test (AET) -The test compares the frequency of overlapping blocks of two adjacent lengths against the expected result for a random sequence. The performance of the file cryptographic transformation is analyzed using the metrics time and throughput [31]. The evaluation parameters are as follows: a) Encryption Time -The required time to process the transformation from plaintext to its equivalent ciphertext and measured in milliseconds.…”
Section: Metricsmentioning
confidence: 99%